Reorienting the Economic Rights of Creators: A Constitutional Analysis of Copyright Licensing Post-Constitutional Court Decision No. 28/PUU-XXIII/2025 - Rifqi Pratama Putra; Dwi Suryahartati; Zeni Sunarti (Rechtsvinding, 2025)
This research examines the implications of Constitutional Court Decision No. 28/PUU-XXIII/2025 on digital copyright licensing in Indonesia. The study addresses the anomaly where rapid creative industry growth fails to enhance creator welfare due to exploitative "direct licensing" mechanisms in Article 40 of Law No. 28 of 2014. This provision is deemed to violate constitutional property rights by allowing digital platforms to exploit works without explicit consent. Using normative legal research with statutory and conceptual approaches, the study analyzes primary and secondary legal materials. The results reveal that Decision No. 28/PUU-XXIII/2025 serves as a constitutional correction, prioritizing substantive justice over industrial efficiency. The ruling strengthens creators' bargaining positions, mandates transparency in royalty systems, and triggers a paradigm shift from efficiency-oriented to justice-oriented licensing. Practical implications include the mandatory renegotiation of licensing contracts, the integration of digital technologies like blockchain within the National Collective Management Organization (LMKN), and the realignment of global platform business models. Ultimately, this decision establishes a robust legal foundation to ensure equitable economic rights protection within Indonesia's digital ecosystem.